(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
EEG-based Brain Computer Interface (BCI) and Transcranial Stimulation represent one of the frontiers in brain studies, promising great potential in practical application in several fields. Indeed, compared to other brain-imaging techniques, BCIÂ and Transcranial Stimulation are non-invasive, low cost and portable, leading to design applications in individuals’ daily life, spreading from health care to politics and defense. Indeed, Science is running fast towards unpredictable results and the implications are global across industries, in every field, but low attention is given to protect individuals’ privacy and wiliness from abuse of data and related information.